IMPROVING READING SKILLS USING THE QUICK READING METHOD IN LEARNING INDONESIAN LANGUAGE SHORT STORY READING MATERIALS CLASS III at SDN Bandung II - Rifki Arif Nugraha; Ratna Dewi (Cakrawala Pedagogik, 2022)
This study aims to determine the improvement of students' reading skills by using the Quick Reading in learning Indonesian short story reading material for class III at SDN Bandung II, Banjar District, Pandeglang Regency. This type of research is a class action research with the John Eliot model using two cycles. The subjects of this study were third grade students of SDN Bandung II for the 2021/2022 academic year, totaling 16 students. Based on the problem formulation regarding students' low understanding of the Indonesian language, it encourages the author to conduct research on how the teacher's efforts to improve understanding in fast reading short story material for elementary school students in this research use the Quick Reading method. This research method refers to the classroom action research design according to John Elliot which includes (1) planning, (2) action, (3) observation, and (4) reflection.The results showed that the use of the quick reading could improve learning activities and students' ability to read short stories. The increase in reading comprehension ability using the quick reading in the first cycle was the initial condition was 67.75 increased to 74.62, the second cycle increased by in the initial condition 74.62 increased to 85.